Assessing competence development and emotional responses during the practical semester of vocational student teachers in Germany - Li, Junmin [Verfasser]; Pylväs, Laura [Verfasser]; Nokelainen, Petri [Verfasser] (My University, 2026)
„In Germany, the integration of practical phases within teacher education programs aims to bridge the gap between theoretical knowledge and practical application. A key initiative is the practical semester, introduced in eleven federal states, which provides experiential learning opportunities supported by university seminars and regional authorities. Research has highlighted a significant correlation between practical training and teachers’ competence development; however, limited studies have addressed the specific experiences of student teachers in relation to their professional competence. This study investigates how vocational education and training (VET) student teachers assess their competencies before and after engaging in school-based activities during this practical semester, with a focus on the emotional responses elicited during these experiences utilising event-contingent diaries and surveys from 23 VET student teachers in North Rhine-Westphalia during the 2023–2024 academic year. The results will provide valuable insights into the interplay between emotional responses and professional development among student teachers during the school practical semester.” (authors’ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; S 1.4 Hochschulbildung; 370; Berufsschullehrer; Lehrerausbildung; Student; Praxissemester; Kompetenzentwicklung; Selbsteinschätzung